Evaluation of the willingness of community pharmacists and community pharmacy owners to provide pharmacy-based immunization services in the City of Manila - Andres, Phillippe Luis C.​; Asilo, Kathrina Michaela M.​; Bondoc, Mark Francis G.​
Widespread immunization is difficult to achieve due to issue on access and patient acceptance. A number of foreign countries, such as, the United States and Canada have successfully addressed access issues on vaccination through the provision of vaccination services by pharmacists at the pharmacy facility. In the Philippines, there are no pharmacies and pharmacists to date that provide immunization services despite the inclusion of this new role of the pharmacists in the new pharmacy law or Republic Act 10918. This study aimed to evaluate the willingness of community pharmacists and community pharmacy owners in providing pharmacy-based immunization services in the City of Manila. The study employed a cross-sectional design which utilized a self-administered questionnaire. Descriptive statistics, chi-square, and tests were used in data analysis. Out of 110 pharmacies selected, only 71.8% pharmacists and 43.6% pharmacy owners agreed to participate, with complete and valid questionnaires. Results revealed that community pharmacists have average knowledge on the basic principles of pharmacy-based immunization services. Both community pharmacists and community pharmacy owners have positive attitude, favorable subjective norms, positive perceived behavioral control, and are willing to provide PBIS. The only variable significantly related to willingness of pharmacists was subjective norm or the perception of other stakeholders to how pharmacy-based immunization services should be performed while there was no variable significantly related to pharmacy owners? willingness to provide PBIS. It is recommended for the Philippine Pharmacists Association (PPhA) to perform interventions to help encourage the pharmacists and owners in providing PBIS. Behavioral studies on the community pharmacist and pharmacy owners in implementing PBIS can be conducted in the future.